Perceptions of Jewish history - Funkenstein, Amos (University of California Press, 1993)
"Perceptions of Jewish History scintillates with original ideas and insights. It will appeal to a broad audience."--Michael A. Signer, University of Notre Dame "Students of the Jewish past will welcome this volume; it will also attract readers with the widest possible range of interests."--Robert Chazan, New York University.